Penegakan Hukum terhadap Pelaku Tindak Pidana Perjudian Online di Kelurahan Tanjung Raja Utara Kabupaten Ogan Ilir - Serlika Aprita; Hasanal Mulkan; Yonani Hasyim; Desni Raspita; Syahriati Fakhriah; Ahmad Muadzdzib; Ilham Mahar Khuluqi; Anela Intan Putri; Fitri Antisa (Fakultas Teknik Universitas Maritim AMNI Semarang, 2024)
The rise of online gambling, which is mostly carried out by lower middle class people, can have a negative impact on the economic development of Indonesia. One of the direct negative impacts of online gambling on the country's economy is that online gambling can reduce state income. This is because the government does not receive taxes from illegal online gambling activities. Apart from that, online gambling can also cause economic losses for society. This legal research aims to find out the factors and how the law is enforced against online gambling players. The type of legal research carried out in this research is normative legal research, namely where law is conceptualized as what is written in statutory regulations (law in the books). ) or law is conceptualized as a rule or norm which is a benchmark for human behavior that is considered appropriate. Based on the research results, it is understood that the factors that cause a person to commit a criminal act of online gambling are influenced by two factors, namely internal and external factors. Internal factors come from within the perpetrator while external factors come from outside the perpetrator, such as the perpetrator's social environment.